Common Thread: The Impact of Mission on Ethical Business Culture. A Case Study - Craft, Jana L. (Journal of business ethics, 2018)
What is the impact of mission on ethical business culture? This question was analyzed through a qualitative case study of a large nonprofit organization in the human services industry with a solid history of ethical business practices and consistent use of a values-based decision-making model. This research explored ethical decision making, ethical business culture, and congruence between enacted and espoused institutional values. Institutional values were identified, and the following pair of research questions was examined: To what extent were incongruent values found between espoused and enacted values? To what extent did incongruent values impact the ethical business culture? Incongruent enacted values were present in the culture, but negative impact was diminished by a larger number of congruent enacted values. Additional findings revealed that an intense commitment to the mission by all employees was the common thread that wound throughout the organization’s ethical business culture and essentially abrogated the undesirable effects of incongruent and negative values.